How to cope the business turbulence: Prospective study of the Mamonal Port in the City of Cartagena (Colombia) (2018)
This paper aimed at applying the methodology of strategic prospective and in a particular way these techniques: MICMAC, MACTOR and SMIC to the Port of Mamonal Port in Cartagena for cope with turbulence environment. The method used was descriptive with a probabilistic sample of 23 employees. Survey and group areas were the methods applied, in three stages or processes: strategic prospective, market analysis and strategic analysis, which allowed establishing future sceneries for the development of the initiatives and projects up to the year 2032. © 2018.